ORGANIC FARMING: A RELIABLE STRATEGY FOR SUSTAINABLE AGRICULTURE IN NEPAL - Sushmita Tiwari; Shreya Rai; Jasmin Adhikari; Samarth Bista (Science Heritage Journal)
Agriculture and agricultural practices should be the wisest pursuits as they contribute to the well-being of Mother Earth. Organic farming is a system of farming that is guided by principles designed to promote environmental conservation, biodiversity, soil health, and the overall well-being of the ecosystem. This comprehensive review delves into the efficacy of organic farming as a dependable strategy for achieving sustainable agriculture in Nepal. Against the backdrop of Nepal’s diverse agroecological zones and traditional farming practices, the study meticulously examines the multifaceted advantages, challenges, and implications of adopting organic farming within this unique context. Organic farming, characterized by the exclusion of synthetic chemicals and the emphasis on ecological balance, stands out as a promising approach to address the pressing issues faced by Nepalese agriculture. The review underscores the enhanced soil fertility associated with organic practices, attributing it to the utilization of natural fertilizers such as compost and manure. This sustainable farming method not only fosters soil health but also safeguards vital resources like water and promotes biodiversity by refraining from synthetic pesticides and fertilizers. With the dawn of the 21st century and the exponential rise in the population, food security has become an alarming issue. To access food demand of the growing population the use of chemical fertilizers has been rampant contributing to sustainability issues. As a result, it becomes increasingly important to address how to achieve food security while simultaneously addressing the imbalance in the ecosystem. In this review paper, we have discussed some of the amendments used for the promotion of organic farming such as Jholmol (1,2,3), Biochar, Panchagavya, Jeevamrut, Bijamrita, Vermin-compost, Vermiwash.